Outpatient versus inpatient cervix priming with Foley catheter: A randomized trial. (March 2017) - Policiano, Catarina; Pimenta, Mariana; Martins, Diana; Clode, Nuno
Abstract: Objective: To compare clinical efficacy between outpatient and inpatient cervix priming with Foley catheter. Study design: We conducted a randomized trial including term pregnancies with a single fetus in cephalic presentation, Bishop score < 6, gestational age > 41 weeks or medical indication for induction of labor. Patients were randomized to outpatient (n = 65) or inpatient (n = 65) priming with Foley catheter. Primary outcome was Bishop score change between outpatient and inpatient groups. Secondary comparisons included: delivery route and catheter application-to-delivery time. Statistical analysis was performed using Student́s t -test and χ2 test. We assessed the contribution of each demographic variable and setting of Foley priming to the variation in induction-to-delivery-time and inpatient time by using multivariate linear regression and the contribution of each demographic variable and setting of Foley to cesarean delivery rate for failed induction by using multivariate logistic regression. p < 0.05 was considered statistically significant. Results: Average Bishop score change was not statistically different between the inpatient and outpatient groups (3.4 vs 2.9, p = 0.37). Outpatient group had a shorter average catheter application-to-delivery time than the inpatient (38.2 vs 44.9. hrs, p = 0.01) and an average of less 10 h of hospital stay than inpatient group. Vaginal birth rate(72% outpatient vs 62% inpatient) was similar between groups. Outpatient group had a statistically significant lower rate of cesarean deliveries for failed induction of labor [2/65 (3%) vs 11/65 (17%), p = 0.02]. There were three cases of chorioamnionitis for each group with no significant maternal or neonatal morbidity. Conclusions: Outpatient priming with Foley catheter is as safe and effective as in the inpatient setting with shorter hospital stay and less cesarean deliveries for failed induction. ClinicalTrials.gov –NCT02842879